Stay of proceedings in Malaysia a lis alibi pendens / Norfini Saad - Saad, Norfini (Faculty of Law, 1987)
A stay of proceedings has always been a controversial issue in the field of law. The courts having the inherent jurisdication to grant a stay of action, sometimes, find it difficult in applying the accepted principles. Conflicting consideration between the plaintiffs and defendants makes it even more so. It is therefore the aim of this Project Paper to discuss cases involving the stay of proceedings , specially those concerning lis alibi pendens. Through out the years numerous cases had developed involving application by litigants for the stay of proceedings. We then began to realise that in the 19th. century, the well known test was the vexatious and oppressive test. However as the law began to expand the Courts started to take a different approach. The forum natural and forum conveniens tests were introduced. The courts then were not hesitant to depart from the old test. However various conflicting grounds made it quite difficult for the Court to find out which test is the most appropriate.